2016
DOI: 10.1515/biol-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH on antioxidant and prooxidant properties of common medicinal herbs

Abstract: Background: We studied in vitro and vivo antioxidant and prooxidant abilities of aqueous extracts from Rosa canina L., Rhodiola rosea L., Hypericum perforatum L., and Gentiana lutea L. Methodology: Total antioxidant capacity was measured by four assays (phosphomolybdate method, Fe3+-reducing activity, ABTS•+ scavenging, H2O2 scavenging). Prooxidant activity was estimated by H2O2 production. Yeast viability in the presence of H2O2 and/or plant extracts was determined by plating or by counting live cells’ number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 48 publications
3
33
1
2
Order By: Relevance
“…Data on the antioxidant activities and total phenolics of the herbs are presented in Table 1. This finding was different from Bayliak et al [10] reporting the increased antioxidant capacities of medicinal herbs in acidic pH solvent. The difference in pH values of media (to dissolve the herbs) seemed to be responsible for the discrepancy results above.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Data on the antioxidant activities and total phenolics of the herbs are presented in Table 1. This finding was different from Bayliak et al [10] reporting the increased antioxidant capacities of medicinal herbs in acidic pH solvent. The difference in pH values of media (to dissolve the herbs) seemed to be responsible for the discrepancy results above.…”
Section: Discussioncontrasting
confidence: 98%
“…Studies showed that the nutritional and functional properties of plant-derived products may be improved through acidification. Sarr and Tsai [9] formerly reported that acidification resulted in higher nutritional factors and antioxidant capacities of tomato juice, while Bayliak et al [10] found the increased antioxidant capacities in medicinal herbs with acidic treatment. In accordance, the solubility and stability of curcumin increased in the acid solution [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that TPC and antioxidant activities were higher ( p < .05) in acidic medium than in the alkaline medium. Decreased antioxidant activity in alkaline medium was attributed to the instability of some phenolic compounds (Bayliak et al., 2016), change in pH or a certain pH may lead to conformational changes of some phenolic constituents in the plant extracts, thus, affecting TPC and antioxidant activities (Friedman & Jürgens, 2000). Results of DPPH‐RSA and FRAP showed parallel trend to that of TPC, in which TPC and antioxidant activities were highest at pH 5 ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, food is intended not only for nutrition, but also for the prevention of chronic and nutrition-related diseases, as well as for improving people's general well-being. In connection with the growing knowledge of consumers about functional food products, new, functional raw materials are being required that contain appropriate phytochemical compounds that help fight diseases or oxidative stress [3][4][5]. One of these raw materials is green barley.…”
Section: Introductionmentioning
confidence: 99%